Kebolehan, Kebaikan Hati dan Integriti Ketua Pasukan Teras Kepercayaan Anggota Dalam Tugas Penguatkuasaan - Azman, Abdul Latiff (2009)
The purpose of this study is to investigate the correlation between team leaders character and trust among the team members of the Enforcement Division of the Ministry of Domestic Trade, Co-operatives and Consumerism Malaysia (MDTCC). This study also aimed at determining whether ability, benevolence and integrity predict the variance in trust among the team members in MDTCC. Out of 392 questionnaires distributed, a total of 207 questionnaires were returned. The data was analyzed using "Statistical Package for Social Science" (SPSS) version 15. Analysis using pearson correlation indicates that all three factors in team leaders character have significant, positive correlation with team members' trust in the leader. In addition, multiple regression analysis shows that only benevolence and integrity significantly can influence team members trust. Analysis using ANOVA shows that no differences between demographic factor with team members trust. Therefore, MDTCC should stress on benevolence and integrity in order to enhance trust among their staff.